Uneconomic Economics and the Crisis of the Model World - Watson, M. author. aut Link
X, 108 p.
Keywords: What has gone wrong with economics? Economists now routinely devise highly sophisticated abstract models that score top marks for theoretical rigour but are clearly divorced from observable activities in the current economy. This creates an 'uneconomic economics', where models explain relationships in blackboard rather than real-life markets.